Trump's Tariff War and Conflict with WTO Principles: Current State and Expected Consequences - Trošić, Sanja Jelisavac; Tošović-Stevanović, Aleksandra (Theoretical and Practical Research in Economic Fields; Vol 16 No 4 (2025): TPREF Special Issue, Volume XVI, Issue 4(36), Winter 2025, 2025)
The research is about a new wave of tariff increases by the US and the conflict of that move in relation to WTO rules and principles. The purpose of the research is to obtain current and new data and information on the changes that the raising of tariffs produced on the international level, especially within the framework of the WTO. The research was approached primarily through document content analysis, data analysis and discourse analysis. Primary and secondary sources were used. The findings of the study show that the sudden change in US tariffs had an impact on the multilateral trading system and on the organization dealing with the regulation of trade rules - the WTO. The WTO had already begun negotiations on reform and modernization, and this new wave of tariffs brought additional uncertainty to all spheres of WTO work. Current and future negotiations are uncertain, and additional research is needed that will point out in detail every aspect of work and problems in the work of the WTO.